Preventive administration of shengmaiyin: a novel approach to counteract heatstroke-induced coagulopathy in rats - He, Longping; Luo, Zhuqing; Zhang, Lichun; Deng, Xingping; Zhong, Lincui; Lin, Qingwei; Zeng, Qingbo; Zhou, Ye; Song, Jingchun (Frontiers in Pharmacology, 2025)
BackgroundCoagulation disorders play a pivotal role in the elevated mortality rates associated with exertional heatstroke (EHS).PurposeTo investigate the impact of Shengmai Yin Oral Liquid (SMY) on heatstroke-induced coagulopathy (HIC) in rats with EHS and to elucidate the underlying mechanisms.MethodsA cohort of eighteen male SPF-grade SD rats, each implanted with a telemetric temperature capsule, were randomly allocated to three groups: a normal control (NC) group, an EHS group, and an SMY group (n = 6 per group). The SMY group received SMY orally at a dosage of 20g/(Kg·day) for a period of five consecutive days. Both the EHS and SMY groups were subjected to exercise in a climate-controlled chamber maintained at 40°C with 70% relative humidity until signs of exhaustion and a core body temperature of 42°C were reached, with the duration and distance of their exercise being meticulously documented. Histopathological assessments were performed on the liver, kidney, lung, duodenum, and heart of the rats. Blood samples were collected to measure prothrombin time (PT), activated partial thromboplastin time (APTT), platelet count, and levels of lactic acid (Lac), thrombomodulin (TM), thrombospondin-1 (TSP-1), von Willebrand factor (vWF), and plasminogen activator inhibitor-1 (PAI-1). Plasma samples were subjected to data-independent acquisition (DIA)-based quantitative proteomics analysis, and differentially expressed proteins identified were further authenticated using parallel reaction monitoring (PRM) and Enzyme-Linked Immunosorbent Assay (ELISA).ResultsThe SMY group exhibited a significantly extended running distance and time before reaching a core temperature of 42°C compared to the EHS group. Histopathological examination revealed thrombosis in the liver, kidney, lung, duodenum, and heart of rats in the EHS group, whereas no significant thrombosis was observed in the SMY group. The EHS group showed significantly prolonged PT and APTT, increased Lac, decreased platelet count, and elevated plasma levels of TM, vWF, TSP-1, and PAI-1 compared to the NC group (P < 0.05). In contrast, the SMY group demonstrated a significant reduction in APTT, an increase in platelet count, and decreased plasma levels of TM, vWF, PAI-1, and TSP-1 compared to the EHS group (P < 0.05). Among the 1,189 proteins identified, 56 differentially expressed proteins (DEPs) were associated with SMY’s protective effects against HIC, primarily involved in the upregulation of the relaxin signaling pathway, protein digestion and absorption, platelet activation, and ECM-receptor interaction signaling pathways, as well as the downregulation of the spliceosome and ribosome signaling pathways. PRM quantitative analysis indicated that SMY may upregulate the expression of Nucleobindin-1 (Nucb1), Procollagen C-endopeptidase enhancer 1 (Pcolce), and lectin galactoside-binding soluble 1 (Lgals1), and downregulate the expression of Xpnpep2. Subsequent ELISA validation confirmed a significant increase in plasma Xpnpep2 levels in EHS rats, an effect that was substantially reduced by pre-treatment with SMY.ConclusionSMY demonstrates the capacity to mitigate HIC by lessening the impact of vascular endothelial damage and moderating the consumption of coagulation factors and platelets. This salutary influence is correlated with the downregulation of XPNPEP2 expression.